Fast grasp planning for hand/arm systems based on convex model - Harada, K.; Kaneko, K.; Kanehiro, F. (2008 IEEE International Conference on Robotics and Automation, 2008)
This paper discusses the grasp planning of a multifingered hand attached at the tip of a robotic arm. By using the convex models and the new approximation method of the friction cone, our proposed algorithm can calculate the grasping motion within the reasonable time. For each grasping style used in this research, we define the grasping rectangular convex (GRC). We also define the object convex polygon (OCP) for the grasped object. By considering the geometrical relashionship among these convex models, we determine several parameters needed to define the final grasping configuration. To determine the contact point position satisfying the force closure, we use two approximation models of the friction cone. To save the calculation time, the rough approximation by using the ellipsoid is mainly used to check the force closure. Additionally, approximation by using the convex polyhedral cone is used at the final stage of the planning. The effectiveness of the proposed method is confirmed by some numerical examples.